Uji Akurasi Jam Bencet dalam Menentukan Awal Waktu Salat Zuhur di Masjid Al-Muttaqin Desa Tanjunganyar Kecamatan Gajah Kabupaten Demak - Ihsan Alwi, Ahmad; Amin, Muhammad Zakiyyul (AL - AFAQ : Jurnal Ilmu Falak dan Astronomi, 2023)
Al-Muttaqin Mosque, Tanjunganyar Village, Gajah District, Demak Regency uses the bencet as a tool to determine prayer times, as its activity refers to the movement of the sun. In fact, the people there dub the bencet as “jam akhirat”. The purpose of this study is 1) to learn how to use bencet to determine Istiwa time, especially midday prayer time at Al-Muttaqin Mosque, Tanjunganyar Gajah Demak village. 2) To find out how accurate the bencet is at the start of determining the istiwa’ time at Al-Muttaqin Mosque, Tanjunganyar Gajah Demak village. This study is a descriptive analytical study in which all data were collected through observation, interviews, and note-taking techniques. Research results show that 1) the method used to determine the initial time for zuhur is referring to the mosque bell and then transforming it into the wall clock. That is, setting the long hand of the wall clock to the number 12 when the mosque bell shows the sun at zawal or the shadow of the gnomon right in the middle of the number 12 on the bell. For this case, 4 minutes of ihtiyat time is added. 2) Compared with the reckoning in Syawariq Al-Anwar's book, there is a difference of 00 0" 33.53' and the formula in the book Ilmu Falak 1 (Penentuan Awal Waktu Salat & Arah Kibat Seluruh Indonesia) has a difference of 00 00' 38.47", so that the jam at the Al-Muttaqin Mosque, Tanjunganyar Gajah Demak Village is classified as Bencet that is still accurate and well maintained.